Stigma and its associations with self-confidence and sexual relations in 4 types of premature ejaculation - Jishuang Liu; Tong Bao; Qunfeng Wang; Hui Jiang; Xiansheng Zhang (Basic and Clinical Andrology)
Abstract Background Although men with premature ejaculation (PE) always show more negative emotions, including embarrassment, guilt and worry, this may be related to the stigma of PE. To investigated stigma and its associations with self-confidence and sexual relations in 4 PE syndromes, a survey was conducted in our hospital from December 2018 to December 2019 among 350 men with self-reported PE and 252 men without self-reported PE. The stigma, self-confidence and sexual relations were assessed by the Social Impact Scale (SIS) and Self-Esteem and Relationship questionnaire (SEAR), respectively. Ejaculation control, sexual life satisfaction and distress caused by PE were evaluated by the Index of PE. Results Men with self-reported PE had higher internalized shame and social isolation scores and lower SEAR scores than control subjects. The highest score of internalized shame and social isolation and the lowest score of SEAR appeared in men with lifelong PE (LPE). After age adjustment, the positive relationships were stronger between distress about PE and internalized shame. Whereas, the stronger negative associations were found between social isolation and sexual satisfaction. The strongest association was observed between social isolation and sexual relationship. Therefore, the stigma associated with PE adversely affects the self-confidence, self-esteem, and sexual relationships of men with PE. Conclusion Men with PE, especially LPE, have a high level of stigma and disharmonious sexual relations, and often lack self-confidence and self-esteem, which have a certain negative impact on their physical and mental health and life. These will be the key issues to be considered when we formulate a personalized treatment plan for PE.